MRI of the Colon in the Pharmaceutical Field: The Future before us - Sarah Sulaiman; Luca Marciani (MDPI AG, 2019)
Oral solid drug formulation is the most common route for administration and it is vital to increase knowledge of the gastrointestinal physiological environment to understand dissolution and absorption processes and to develop reliable biorelevant in vitro tools. In particular, colon targeted drug formulations have raised the attention of pharmaceutical scientists because of the great potential of colonic drug delivery. However, the distal bowel is still a relatively understudied part of the gastrointestinal tract. Recently, magnetic resonance imaging (MRI) has been gaining an emerging role in studying the colon. This article provides a comprehensive; contemporary review of the literature on luminal MRI of the colonic environment of the last 15 years with specific focus on colon physiological dimensions; motility; chyme and fluids; transit and luminal flow. The work reviewed provides novel physiological insight that will have a profound impact on our understanding of the colonic environment for drug delivery and absorption and will ultimately help to raise the in vitro/in vivo relevance of computer simulations and bench models.